Analysis of Technology Support Needs in Foreign Language Learning Models for Learners with Disabilities to Support the Independent Learning Vocational Program - Prasetyo Ery, Anda; Mukarramah Machmud; Muhammad Said; Muhammad Salim, Muhammad Arfin (Eduvelop: Journal of English Education and Development, 2026)
The Independent Learning (Vocational) Program requires independence and practical skills, such as foreign language proficiency. To ensure that students with disabilities, particularly students who are Deaf (total deafness), can participate in the vocational environment, this study examines the necessary adaptive technologies and strategies. Limited participatory observation in the model trial class and document analysis (RPS and curriculum) were used in this qualitative case study. The focus of the observation was the use of visual media and technology, as well as identifying gaps in existing technological support. The results show that using a learning model is very effective in low-tech visual adaptation driven by lecturers' personal efforts. This includes the preparation of adaptive lesson plans (RPS), captioning, and consistent visualization. However, the analysis found that the high-tech gap results in a significant need for technological support (A4). There are certain communication barriers, particularly in verifying students' spontaneous cues (C1), because real-time voice-to-text conversion applications are not explicitly supported by the curriculum guidelines. To address miscommunication, the integration of real-time assistive tools is a top technological need. To achieve the goal of vocational program independence, adaptive practices must be reinforced with institutional policy mandates that ensure adaptive technology is available and used so that inclusion no longer depends on individual faculty autonomy.